Analisis Hukum Terhadap Praktik Insider Trading di Pasar Modal Indonesia: Tantangan dan Solusi - Alexander Kennedy; Sophia Al Hikmah; Ida Bagus Gede Satya Wibawa Antara (Fakultas Hukum, Universitas Warmadewa, 2024)
Indonesia's capital market has experienced significant growth, becoming a crucial pillar in supporting the national economy. However, maintaining market integrity and public trust is essential, as unfair trading practices like insider trading undermine transparency and fairness. Insider trading, involving the use of non-public material information for personal gain, continues to challenge Indonesia’s regulatory environment despite legal frameworks such as the Capital Market Law (Law No. 8 of 1995) and OJK regulations. This study aims to provide a comprehensive legal analysis of insider trading practices in Indonesia's capital market by identifying enforcement challenges, examining regulatory weaknesses, and proposing strategic solutions. Using a normative juridical approach with case studies, this research investigates real insider trading cases and evaluates regulatory and enforcement gaps. Findings indicate that limited resources, technological constraints, and unsynchronized regulations hinder effective enforcement. Furthermore, cultural factors such as low ethical awareness and prevalent nepotism in business exacerbate the issue. The study recommends strengthening regulations, investing in advanced monitoring technologies, and fostering ethical awareness among market participants. These measures are essential for building a fairer and more transparent capital market. Enhanced law enforcement, combined with cultural shifts towards ethical business practices, can protect market integrity, foster investor trust, and contribute to Indonesia’s economic stability and growth. This research contributes valuable insights to policymakers, regulators, and capital market stakeholders in developing a stronger legal and operational framework against insider trading in Indonesia.